Inequalities in Islamic State and Society: A Critical Review on the Thoughts of Bernard Lewis - Yasir Farooq,; Ghauri, Ihsan Ur Rahman (Journal of Islamic and Religious Studies, 2017)
Islam and the West are two competitor civilizations of 21st century. West is much fear by the rapid expansion of Islam. It is imagined that very soon Islam is going to become a major religion of the Europe. Now European think tanks are constantly working to present a negative picture of Islam. Bernard Lewis is trying his best to prove that Islam is not a suitable civilization and religion for the world. As there are different classes of citizens within Islamic State and society and all the citizens are not equal in Islamic teachings and practice like women, slaves and Non-Muslims. Whereas, his presented theories are quite different than real teachings and practice of Islam. All the citizens of Islamic State are equal before law but there is difference of responsibilities according to their abilities. This article is presenting a critical and real discussion about the social inequalities blamed by Bernard Lewis, existing in Islamic state and society.